Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prove that

$${e^{-1} =2(\frac{1}{3!} + \frac{2}{5!} + \frac{3}{7!} + \frac{4}{9!} ....)}$$.

I am unable to solve it. I know I have to solve it using expansion of ${e^x}$.But I am unable to understand the algebraic manipulation that I have to perform to solve it. Please help me. Thank you! :))

share|cite|improve this question
What are the next terms? – Did May 3 '14 at 13:56
Giving just 2 terms isn't enough, please add a few more or write a formula. – user88595 May 3 '14 at 13:57
I think it may be $\frac{r}{(2r+1)!}$ – evil999man May 3 '14 at 13:59
Did you miss a + sign? – evil999man May 3 '14 at 13:59
up vote 12 down vote accepted

$$\begin{align}e^{-1}&=\sum_{n=0}^\infty\frac{(-1)^n}{n!} \\&=\sum_{n=0}^\infty\left(\frac{(-1)^{2n}}{(2n)!}+\frac{(-1)^{2n+1}}{(2n+1)!}\right)\\&=\sum_{n=0}^\infty\frac{(2n+1)-1}{(2n+1)!}\\&=2\sum_{n=0}^\infty\frac{n}{(2n+1)!}\\&=2\sum_{n=1}^\infty\frac{n}{(2n+1)!}\end{align}$$

share|cite|improve this answer
Two bottom expressions are identical. Did you mean to have $2$ inside the sum in the pre-last one? – Ruslan May 3 '14 at 14:49
@Ruslan Not identical. $n=0\to\infty$ in the first, but $n=1\to\infty$ in the second. – Justin May 3 '14 at 16:27
Ah, didn't notice this. – Ruslan May 3 '14 at 16:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.